2004
DOI: 10.1055/s-2004-815773
|View full text |Cite
|
Sign up to set email alerts
|

Necessity for Surgery in Children with Gastrooesophageal Reflux and Supraoesophageal Symptoms

Abstract: The results of this study stress the importance of symptoms, clinical response to anti-reflux medical treatment and broncho-alveolar lavage compared to classical pH parameters in the decision-making process for patients with difficult-to-treat supraoesophageal symptoms. To date no single tool alone has proved to be diagnostic in these patients. Fundoplication is recommended only when a relationship between supraoesophageal symptoms and gastrooesophageal reflux is strongly suspected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Another possible application for HRM is in the pre- and post-operative evaluation of children undergoing fundoplication for the treatment of GERD. Although previous studies suggested that there was little role for manometry in predicting the outcome of fundoplication (64), newer modalities may confer some practical benefit. Loots et al, for example, used a novel pressure-flow analysis technique to identify esophageal motility parameters that are associated with post-operative complications such as dysphagia.…”
Section: Question 3: What Diagnostic Interventions Have Additional Vamentioning
confidence: 97%
“…Another possible application for HRM is in the pre- and post-operative evaluation of children undergoing fundoplication for the treatment of GERD. Although previous studies suggested that there was little role for manometry in predicting the outcome of fundoplication (64), newer modalities may confer some practical benefit. Loots et al, for example, used a novel pressure-flow analysis technique to identify esophageal motility parameters that are associated with post-operative complications such as dysphagia.…”
Section: Question 3: What Diagnostic Interventions Have Additional Vamentioning
confidence: 97%